Including the online feedback site, Patient Opinion, in the nursing curriculum: Exploratory study. (October 2017) - Jones, Ray; Young, Kim; Munro, James; Miller, Heather; Brelsford, Stephanie; Aronsson, Jennie; Goodman, Benny; Peters, Jane
Abstract: Background: Globally, universities aim to involve people who use health services to enrich the nursing curriculum for students, but there can be barriers to this involvement. Many also want students to contribute to local communities. Online communication can help connect students to service users to achieve these aims. The online British patient feedback site, Patient Opinion, gathers comments from service users about services and encourages service responses to the comments. Objectives: To explore the feasibility and acceptability of five ways of including Patient Opinion in the undergraduate nursing curriculum. Design: Five case studies using mixed data collection methods. Settings: British University with nursing students across two campuses, accustomed to using webinars, video presentations and social media. Participants: Students from different years participated in the five approaches of making use of Patient Opinion in the curriculum; 18 students took part in an online forum to discuss Patient Opinion in the curriculum. Methods: We trialled timetabled webinars, video-linked lectures, optional enhanced access for self-study, optional audit of service user comments for two local hospitals, and optional Twitter and Tweetchat. Students discussed the aims and approaches in an online forum. Results: Of the five approaches trialled, webinars seemed effective in ensuring that all nursing students engaged with the topic. Video-linked lectures provided an alternative when timetabling did not allow webinars, but were less interactive. The three optional approaches (Tweetchats, audit exercise, self-directed study) provided opportunities for some students to enhance their learning but students needed guidance. Sending a summary of student reviews of patients' feedback to local hospitals illustrated how students might be agents of change in local health services. Conclusions: Experience from these case studies suggests that webinars followed by use of Patient Opinion preparing for placements may be a sustainable way of embedding feedback sites in the nursing curriculum. Highlights: Involving patients may enrich the curriculum and contribute to local communities. Patient Opinion gathers comments from patients about services. We trialled 5 methods of using Patient Opinion in the nursing curriculum. Students thought it worthwhile; webinars were a good introduction. More work between students and Patient Opinion helping local communities is needed.